(untitled) (Journal of the College of Basic Education, 2023)
The two micro algae chlorella & Scenedesmus were used in purification of wastewater with investment of sludge bacteria existing in the same water. The two algae were isolated from Tigris river startly them grown in medium prepared in the lab independent on the water of the river as a basic medium in order to use these growths as algal inoculums in the later experiments. These algae were tried to grow on the samples of wastewater in Baghdad to produce a biomass utilized as a source of food and feed. Lab experiments were achieved to study the effect of temperature, conc. of salt and shaking period on the extraction of protein taken from the mass of algal growth.